EFFECT OF ANTIHYPERTENSIVE THERAPY ON METABOLIC PROFILE AND ERECTILE FUNCTION IN HYPERTENSIVE MEN WITH HIGH CARDIOVASCULAR RISK: FOCUS ON THE COMBINATION OF LISINOPRIL AND AMLODIPINE - M. N. Mamedov; M. V. Stroeva; M. N. Kovrigina; E. A. Poddubskaya (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study the antihypertensive and metabolic effects of lisinopril plus amlodipine combination in hypertensive men with high cardiovascular risk.Materials and methods. Hypertensive men (n=21) with high cardiovascular risk (SCORE scale >5%) aged 30-59 y.o. were included in the study. Questionnaire survey, blood pressure (BP) and heart rate measuring, anthropometric studies, evaluation of the plasma lipid profile, uric acid level and glucose tolerance test were performed at baseline and at the end of the study. Erectile function was assessed by International index of erectile function (IIEF) score. After the cancellation of previous antihypertensive drugs patients were prescribed lisinopril 10 mg QD and amlodipine 5 mg QD. The duration of the study was 6 months.Results. In 4 weeks of the treatment systolic and diastolic BP decreased by 9.3 and 5.2%, and in 24 weeks – by 14.7 and 7.2% respectively (p<0.05). Target BP levels were achieved in 85% of patients. Antihypertensive therapy during 6 months had no significant effect on the plasma lipid profile, glucose and uric acid levels. The mild to moderate-mild erectile dysfunction were detected in 35% of men before therapy. Erectile function indices in hypertensive men with high cardiovascular risk had not changed during combined antihypertensive therapy.Conclusion. Antihypertensive therapy with lisinopril and amlodipine in hypertensive men with high cardiovascular risk during 6 months led to a statistically significant reduction of BP level without affect plasma lipid profile, glucose and uric acid levels as well as erectile function.